‘Contrarie to the Directorie’: Presbyterians and People in Lancashire, 1646–53 - Craven, Alex (Studies in church history, 2007)
In 1645, Parliament swept away the Anglican liturgy of the Church of England, replacing the Book of Common Prayer with a new Presbyterian alternative, the Directory. The Episcopal hierarchy of the Church had already been demolished, and it was expected that the national Church would be reformed along puritan lines. The campaign to impose Presbyterian discipline in England, and the concomitant struggle for a reformation of manners, has received much attention from historians. There is little doubt that nationally these new measures failed, with John Morrill asserting that ‘these ordinances were not only largely ignored but actively resisted’. Presbyterian classes were successfully erected in a handful of places, however, including Lancashire. This should not surprise us, given the county’s long reputation for Puritanism. Nine classes were created at Manchester, Bury, Whalley, Warrington, Walton, Leyland, Preston, Lancaster and Ulverston, and a Provincial Assembly met at Preston. The full minutes of Manchester and Bury classes, and the several extant sets of churchwardens’ accounts, offer a fascinating insight into the workings of this new system. The popular reaction to the new order is also demonstrated; people who travelled to banned services demonstrated where they stood on the liturgical divide, as did those who presented offenders for punishment. This essay, therefore, seeks to evaluate the efforts to erect Presbyterianism within a county where we might reasonably expect it could succeed. The outcome of this struggle will tell us much about the chances of a national Presbyterian Church of England’s survival.